PELAKSANAAN GERAKAN INFAQ HARIAN SEBAGAI SARANA EDUKASI FILANTROPI ISLAM PADA SISWA SDN KEPANJEL KIDUL 1 KOTA BLITAR - Rifa’i, Akhmad; Rakhmad widi Ashari, Denny; Basid Al Haris , Mohammad; Sastra Waskita, Gautama (Izdihar: Jurnal Ekonomi Syariah, 2025)
The phenomenon of declining social concern among the younger generation highlights the growing importance of instilling character education based on religious values from an early age. One form of implementing these values is the daily infaq movement carried out in elementary schools. This study was conducted at SDN Kepanjenkidul 1, Blitar City, which regularly organizes an infaq program every Friday along with a daily savings activity managed by classroom teachers. The program functions not only as a social activity but also as an educational medium for Islamic philanthropy that is relevant to students’ character formation. This research employed a descriptive qualitative approach. The subjects consisted of 70 students (34 boys and 36 girls) and 8 teachers. Data were collected through observation, interviews, and documentation, then analyzed using the interactive analysis model of Miles & Huberman, which includes data reduction, data display, and conclusion drawing.The findings indicate that the daily infaq activity generates an average fund of IDR 24,000–30,000 per week, managed simply yet transparently by the classroom teachers. Moreover, the daily savings program contributes to training students in personal financial management and promoting a thrifty lifestyle. Teachers perceive this activity as effective in developing caring attitudes, a spirit of sharing, and a sense of togetherness among students.Thus, the implementation of the daily infaq movement at SDN Kepanjenkidul 1, Blitar City, has proven to be not only socially beneficial but also educationally significant. This program successfully internalizes religious, social, economic, and character values simultaneously, making it a potential model for Islamic philanthropic education in elementary schools